Tracer gas mapping of beverage cart wake in a twin aisle aircraft cabin simulation chamber - Trupka, Andrew Tristan (Kansas State University, 2011)
In 2010, over 786 million passengers flew on commercial flights in the United States according to the Bureau of Transportation Statistics (2011). With the average flight length over 1300 miles for domestic flights, this amounts to billions of hours spent aboard airliners by passengers each year. During these flights, diseases and other harmful contaminates, some malicious, can spread throughout aircraft cabins, harming passengers. Aircraft ventilation systems are designed to remove these harmful contaminates as quickly as possible to minimize spread in cabin air. Disruptions to the design airflow pattern can hinder the effectiveness of contamination removal efforts. A common form of this airflow disruption is longitudinal air movement through cabin aisles. To examine the effect of contaminate transport down aircraft aisles by a moving body, a motorized beverage cart is past by a contamination source as it traverses the length of the cabin aisle. An experimental study is performed in a mockup Boeing 767 cabin section consisting of eleven rows with seven seats per row. Carbon Dioxide (CO2) tracer gas is injected at a constant flow rate at a location of interest until concentrations in the cabin reach steady state. Ventilation equipment and flow rates representative of an actual aircraft are used for all experiments. Seats in the mockup are occupied by thermal manikins to simulate passenger heat load. A motorized beverage cart traverses the length of the cabin aisle passing by the injection location. The concentrations of tracer gas displaced by the cart are measured at locations throughout the cabin. Comparing these measurements to baseline readings taken with no cart movement, a map of the degree to which contaminant transport is affected by the beverage cart is calculated. The cabin mockup is supplied by 100% outdoor air through actual Boeing supply ductwork and linear diffusers along the cabin length above the aisles. The CO2 level is measured in the inlet air, measurement locations in the cabin, and exhaust air using nondispersive infrared (NDIR) sensors. Measured results are reported for all (54) seat locations downstream of the cart traverse/injection location for an injection location near the rear of the cabin. Analogous measurements are also conducted examining the effect of variations in cart speed and modified injection location. It was found the beverage cart movement had an effect of up to a 35% increase in tracer gas concentration relative to the local steady state concentration for several seat locations adjacent to the aisle. This increased concentration continued for only a few minutes in all cases, but was generally less than the steady state exposure one row closer to the injection location. Moving in the lateral direction away from the aisle, the variance in tracer gas concentration due to the cart movement diminished quickly. The significance of increased concentration for such short periods of time in comparison to the length of actual commercial flights may require further biological analysis. The data showed general tracer gas concentration increases due to cart movement in a small section of the cabin mockup which could warrant further analysis, but increases were generally insignificant when considering entire flight contamination exposure levels.
Keywords: Airliner aisle movement; Aircraft disease spread; Mechanical Engineering (0548)